AB0202 Low dose acetylsalicylic acid as primary prophylaxis of cardiovascular events in rheumatoid arthritis. a longitudinal, retrospective study. (15th June 2017) - Iacono, D; Fasano, S; D'Abrosca, V; Pantano, I; Chieffo, R; Valentini, G
Abstract : Background: Cardiovascular events (CV) i.e. acute myocardial infarction and stroke are recognized as a leading cause of mortality in patients with Rheumatoid Arthritis (RA) [1, 2]. Acetylsalicylic acid (ASA) is known to be associated with a significant decrease in the incidence of CV events in patients at high risk for atherosclerosis like patients with diabetes [3] and has been recently reported to play a primary prophylactic role of CV events in Systemic Lupus Erythematosus by our team [4]. Objectives: To investigate the so far unexplored role of ASA in reducing CV morbidity in RA. Methods: We analysed patients admitted to our Outpatient clinic from January to December 2015. Out of 199, 155 patients, who had been followed from January 2000 and had not experienced any CV event at the first visit, were enrolled. The incidence of CV morbidity was recorded at December 2016. Results: The 155 patients had been followed-up for a median of 8 years (range 1–15 years). Out of them, 111 patients had been treated with ASA, that we currently administer to patients undergoing steroid treatment. During the 15-years of follow up, 5 CV events (2 cerebrovascular, 3 acute myocardial infarction) had occurred (Incidence rate 3.93/1000 person/year). Interestingly, only 1 CV event had occurred in ASA treated patients (Incidence rate 1.12/1000 person/year) with respect to 4 in the non-ASA group (44 patients) (Incidence rate 10.48/1000 person/year) (p=0.0146). Conclusions: Our study has several limitations including the low number of patients and CV events. Nevertheless, it might suggest a primary prophylactic role of ASA in RA, that awaits to be investigated in large controlled prospective studies. References: Arthritis Rheum. 2001 Dec;44(12):2737–45. High incidence of cardiovascular events in a rheumatoid arthritis cohort not explained by traditionalcardiac risk factors. del Rincόn ID, Williams K, Stern MP, Freeman GL, Escalante A. BMC Musculoskelet Disord. 2014 Apr 29;15:142. Cardiovascular case fatality in rheumatoid arthritis is decreasing; first prospective analysis of a current low disease activity rheumatoid arthritis cohort and review of the literature. Meek IL, Vonkeman HE, van de Laar MA. Diabetes Res Clin Pract. 2016 Oct;120:31–9. Aspirin for primary prevention of cardiovascular disease in patients with diabetes: A meta-analysis. Kokoska LA, Wilhelm SM, Garwood CL, Berlie HD. Rheumatology (Oxford). 2016 Sep;55(9):1623–30. Low-dose aspirin as primary prophylaxis for cardiovascular events in systemic lupus erythematosus: a long-term retrospective cohort study. Iudici M, Fasano S, Gabriele Falcone L, Pantano I, La Montagna G, Migliaresi S, Valentini G. Disclosure of Interest: None declared